Generational Differences in Tourism Participation – A Convergence Analysis in the Aspects of SDG and Social Cohesion - Stanimir, Agnieszka (Publishing House of Wroclaw University of Economics and Business, 2025)
The changes in the structure of the EU society correspond to the global trend of ageing populations. This results in the need to adapt many areas of life to the needs reported by current seniors and prepare for future seniors’ needs. The study focused on the participation of European seniors and pre-seniors in tourism. Research on the economies of EU countries indicates the occurrence of conditional convergence, which may translate into the unified quality of citizens’ life. The study used data on participation in tourism and the financial situation of the aforementioned social groups. Time series clustering was used as the method of analysis. As a result, groups of EU countries with a convergent perception of participation in tourism and the financial situation of seniors and pre-seniors were identified.
Quote as: Stanimir, A. (2025). Generational Differences in Tourism Participation – A Convergence Analysis in the Aspects of SDG and Social Cohesion. In B. Drelich-Skulska, M. Sobocińska, & A. Tomášková (Eds.), Sustainable Development in Light of Research by Scientists from Poland, Czechia and Slovakia. Different Research Perspectives (pp. 195-207). Publishing House of Wroclaw University of Economics and Business.
Keywords: senior's activity in tourism; convergence; social cohesion; ageing society